Influences of drive torque distribution on road vehicle handling and efficiency - Griffin, Joseph W. (2015)
With recent developments in active vehicle drivelines and the trend towards the use of electric propulsion in road vehicles, the optimal way to distribute power in a vehicle has become an interesting area of research. Automobiles with Active Torque Distribution (ATD) capabilities demonstrate improved handling and stability, and there is the possibility that energy consumption could be reduced through better distribution of power. Motorcycles that can apply some of the drive torque at the front wheel exist, with the aim of increasing tractive force on low-friction surfaces. Research is required to investigate the effects of torque distribution on the handling and efficiency of motorcycles and automobiles.